Investigating Elevated E-Selectin and P-Selectin Levels in Non-Arteritic Anterior Ischemic Optic Neuropathy (NAION) Patients: The Stepping Stone to a Future Clinical Approach - Syntia Nusanti; Andhika Rachman; Brigitta Marcia Budihardja; Lourisa Ruth Eldinia; Nadia Delima Andini; Arief Kartasasmita; M Sidik; Seskoati Prayitnaningsih; Alida Roswita Harahap; Aria Kekalih; Tjahjono Darminto Gondhowiardjo (Acta Medica Indonesiana)
Background: Studies regarding hypercoagulation in Non-Arteritic Anterior Ischemic Optic Neuropathy (NAION) patients have produced conflicting results. With a presumption that the early coagulation phase may affect the occurrence of NAION, this study aims to investigate the early coagulation markers, E-selectin and P-selectin, to determine whether these biomolecular changes play a significant role in NAION, thus potentially leading to a better clinical approach. Methods: A cross-sectional study involving two groups of NAION subjects, a hypercoagulation group and a non-hypercoagulation group, was conducted in the Neuro-Ophthalmology Division, Department of Ophthalmology, FKUI-RSCM Kirana from October 2020 to April 2022. All patients were evaluated for E-selectin and P-selectin levels measured using flow cytometry.  Results: A total of 42 subjects comprising 14 hypercoagulation and 28 non-hypercoagulation subjects were included. In all subjects, E-selectin was strongly correlated with P-selectin (r = 0.862, p < 0.001). There was no significant difference in E-selectin and P-selectin values between the groups (p = 0.317 for E-selectin, and p = 0.575 for P-selectin). Prothrombin time and international normalized ratio (INR) were inversely correlated with both E-selectin and P-selectin in the hypercoagulation group (p = 0.032, p = 0.030 for E-selectin and p = 0.044, p = 0.036 for P-selectin). There was no significant correlation between E-selectin and P-selectin for NAION-associated metabolic risk factors. However, higher E-selectin and P-selectin values were found in the presence of risk factors except for P-selectin in the hypertension group. Conclusion: This interesting finding opens up the potential for considering the involvement of E-selectin and P-selectin in the diagnostic strategy for NAION. It prompts consideration of whether assessing E-selectin and P-selectin levels should be recommended for all NAION patients. Furthermore, considering the role of E-selectin and P-selectin in the early coagulation process, future studies are also needed to further evaluate whether anticoagulants could play a role in the choice of treatment for NAION despite a clinically hypercoagulable state.